The Operationalization of the Concepts of Political Hegemony and the Power Bloc: Elements for a Theoretical Redefinition - Cintra Lima, Gustavo dos Santos; Gil, Aldo Duran (Pontifícia Universidade Católica de São Paulo, 2015)
This article seeks to briefly examine the proposals offered by Décio Saes for the operationalizationof the concepts of political hegemony and the power bloc, which were formulated byPoulantzas in Political Power and Social Classes, originally published in 1968. Saes appliesthe poulantzian theoretical scheme, with a number of corrections, in order to analyze theoperation of the modern Brazilian slave state and its destruction (=political revolution) duringthe transition to the dominance of capitalist production relations in Brazilian society in the latenineteenth century.